Avaliação da satisfação dos médicos do programa mais médicos - Benevides, Philipe Meneses (2019)
The shortage of doctors and their poor distribution in Brazil are part of the set of challenges for the qualification of the Sistema Único de Saúde (Unified Health System). The Mais Médicos (More Doctors) Program was instituted with the aim of guaranteeing the effective provision of physicians to the priority areas and reduction of regional inequalities. Despite opposition from medical entities, especially in the implementation of the program, this was sustained and solidified as the studies demonstrate improved health outcomes, and increased user and professional satisfaction. In order to guarantee the attraction and fixation of physicians in Primary Care in the long term, it is necessary to study their satisfaction with the Mais Médicos Program, in order to offer subsidies for the decision-making of the managers for future actions with these ends. Thus, a quantitative research was performed based on secondary data from a physician satisfaction assessment instrument inserted in the Mais Médicos Program in the state of Paraíba. This instrument generated a database with data from 249 respondents, whose results gave rise to analyzes divided into two articles. This evaluation of the work of the physicians in the programs shows a good level of satisfaction, with a high indication of permanence in the program and in the work in Primary Care. The proposed satisfaction model was composed of 49 indicator variables grouped into six dimensions: drugs, structure, aspects of the More Medical Program, support, printed matter and equipment. The present study verified the best evaluated items and factorial structure of a strategic questionnaire for other researchers to study the satisfaction of the physician who works in health systems. It also enables managers to find ways to reduce the turnover of health professionals, achieving lower costs and offering better health care for a population.